2011
DOI: 10.4314/ahs.v11i3.70064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative status in patients with <i>Fasciola hepatica</i> infection

Abstract: AbsractBackground: F. hepatica infection is rare and mostly subclinical. Migration of juvenile forms of F. hepatica into the host's liver is accompanied by an inflammatory reaction followed by fibrosis and cirrhosis. Objective: The aim of this study was to evaluate oxidative status by using a novel automated method in patients with Fasciola hepatica. Methods: Twenty two patients with a diagnosis of F. hepatica and 26 healthy volunteers were enrolled in the study. Their Total antioxidant capacity status (TAC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Oxidative stress has an important role in the pathogenesis of viral hepatitis, sepsis and bacterial infections (13,14). Liver enzymes (ALT, AST, GGT), oxidative stress index-OSI and TOS increases are marked in animals with fascielosis, while TAS decreases in serum and plasma samples (15). In this study, the levels of TAS and TOS were increased in the peritoneal fluid compared with serum samples (Table 3) and some data supported our findings (14,16).…”
Section: Discussionsupporting
confidence: 79%
“…Oxidative stress has an important role in the pathogenesis of viral hepatitis, sepsis and bacterial infections (13,14). Liver enzymes (ALT, AST, GGT), oxidative stress index-OSI and TOS increases are marked in animals with fascielosis, while TAS decreases in serum and plasma samples (15). In this study, the levels of TAS and TOS were increased in the peritoneal fluid compared with serum samples (Table 3) and some data supported our findings (14,16).…”
Section: Discussionsupporting
confidence: 79%
“…Another study that investigated the oxidative status in Fasciola hepatica infections showed that plasma TOS levels and the oxidative stress index (OSI) were significantly increased in infected patients than in healthy controls. In contrast, they found that TAC levels were significantly lower in patients than in controls (19). CCHF may be possibly related to increased free radical production and antioxidant depletion, and oxidative stress may be implicated in CCHF pathogenesis.…”
Section: Introductionmentioning
confidence: 88%
“…Studies have reported that CAT is a major intracellular antioxidant enzyme (Aslan et al 2007;Simsek et al 2006) although, Karsen et al (2011) reported that CAT activity was found to be unimportant in fascioliasis since no statistically significant difference was available between patients and control groups (Ece et al 2006). LPO is an ongoing physiological process, but several lines of evidence have suggested an important role for peroxidation in the pathogenesis of several parasitic diseases (Erel et al 1997;Karsen et al 2011;Oliveira and Cechini 2002). LPO caused by ROS results in the disarrangement and ultimately, disruption of cell membranes, which leads to necrotic death (Bagchi et al 1993).…”
Section: Discussionmentioning
confidence: 99%